Evidence of prevailing practice of home slaughter in Iran revealed by bioeconomic modeling of small ruminants slaughtered in and outside registered abattoirs - Mohammad Ebrahimipour; Mehdi Borhani; Omid Dayani; Majid Fasihi Harandi (PLoS ONE, 2026)
Home slaughter seems to be a prevailing practice in developing countries, and presents a potential public health risk and animal welfare problem for the societies all over the world. Nevertheless, the nature and extent of this practice is poorly understood in many countries. The objective of this study was to estimate the number of sheep and goats slaughtered outside registered abattoirs in Iran and to discuss the possible determinants of this practice. Number of live and slaughtered animals, human population, and per capita red meat consumption were extracted from FAOSTAT and the Statistical Center of Iran (SCI). Per capita red meat consumption and bio-economic modeling of flock compositions were used to estimate non-abattoir slaughter numbers. Based on per capita meat consumption and the bio-economic models, it was estimated that 7,937,725 (42.3%) and 12,809,170 (54.1%) of sheep and goats were slaughtered either at home or in unregulated abattoirs during 2017. Home slaughter is a neglected problem in numerous countries and communities. Additional studies are needed to clarify the nature and extent of this human and livestock health challenge. An integrated One Health surveillance system is needed to address this practice in developing countries.